Analisa Pengetahuan, Sikap, Fasilitas Sekolah Terhadap Tindakan Mengurangi Penggunaan Plastik Sekali Pakai di Sekolah Menengah Pertama - Siti Muti’ah; Vita Pramaningsih; Rusdi (Poltekkes Kemenkes Semarang, 2026)
Plastic waste and microplastics are an increasingly serious environmental problem due to the high use of single-use plastics, particularly in school environments. This condition not only causes environmental pollution but also poses potential risks to the health of living organisms. This study aims to analyze the relationship between knowledge, attitudes, and school facilities and students' actions in reducing single-use plastic consumption among MTs and Muhammadiyah Junior High School students in Samarinda City. This study used a quantitative design with a cross-sectional approach. A total of 236 respondents were selected using a cluster sampling technique. Data were collected through questionnaires measuring students' knowledge, attitudes, perceptions of school facilities, and actions, as well as observation sheets to verify the actual availability of school facilities. Data were analyzed using the Chi-Square test and Fisher's Exact Test at a significance level of 0.05. Statistical analysis showed no significant relationship between knowledge and action (p=0.366), whereas significant relationships were found between attitudes and action (p=0.025; PR=6.740) and between school facilities and action (p=0.043; PR=2.571). These findings indicate that students' actions in reducing plastic use are more strongly influenced by attitudes and the availability of school facilities than by knowledge. This study concludes that there is a significant relationship between attitudes and school facilities and students' actions in reducing single-use plastic use, suggesting that improving school facilities and strengthening positive attitudes should be prioritized in efforts to reduce single-use plastic in school environments.